2019
DOI: 10.21608/ajs.2019.43358
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plant Growth-Promoting Rhizobacteria on Cowpea Growth Performance and Root Diseases Controlling Under Greenhouse Conditions

Abstract: This study was executed during two successive seasons 2014 and 2015 for evaluating the effect of inoculation with Bradyrhizobium sp, Bacillus megaterium, Bacillus circulans, Glomus macrocarpum and Pseudomonas fluorescens on infection percentage, enzymatic activity, growth characteristics, total phenol, peroxidase and polyphenol oxidase activity in presence or absence of Fusarium oxysporum in sterilized or non-sterilized soil under greenhouse condition. The obtained results observed that the tested strains show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…These strains also improved cowpea plant growth by inducing resistance against CBMV, under laboratory and field conditions. Zaghloul et al (2019) showed that the PGPR strains used are good for fertilization management and bio-control which reduce the amount of NPK chemical fertilization. The research work conducted by Rocha et al (2019) revealed that cowpea fields could perform better if PGPR seed and AM fungal isolates were used in low-input farming systems.…”
Section: Plant Growth-promoting Rhizobacteria (Pgpr)mentioning
confidence: 99%
“…These strains also improved cowpea plant growth by inducing resistance against CBMV, under laboratory and field conditions. Zaghloul et al (2019) showed that the PGPR strains used are good for fertilization management and bio-control which reduce the amount of NPK chemical fertilization. The research work conducted by Rocha et al (2019) revealed that cowpea fields could perform better if PGPR seed and AM fungal isolates were used in low-input farming systems.…”
Section: Plant Growth-promoting Rhizobacteria (Pgpr)mentioning
confidence: 99%